A comparative historical and demographic study of the neuromodulation management techniques of deep brain stimulation for dystonia and cochlear implantation for sensorineural deafness in children. (January 2017) - Hudson, V.E.; Elniel, A.; Ughratdar, I.; Zebian, B.; Selway, R.; Lin, J.P.
Abstract: Cochlear implants for sensorineural deafness in children is one of the most successful neuromodulation techniques known to relieve early chronic neurodisability, improving activity and participation. In 2012 there were 324, 000 recipients of cochlear implants globally. Aim: To compare cochlear implant (CI) neuromodulation with deep brain stimulation (DBS) for dystonia in childhood and explore relations between age and duration of symptoms at implantation and outcome. Methods: Comparison of published annual UK CI figures for 1985–2009 with a retrospective cohort of the first 9 years of DBS for dystonia in children at a single-site Functional Neurosurgery unit from 2006 to 14. Results: From 2006 to 14, DBS neuromodulation of childhood dystonia increased by a factor of 3.8 to a total of 126 cases over the first 9 years, similar to the growth in cochlear implants which increased by a factor of 4.1 over a similar period in the 1980s rising to 527 children in 2009. The CI saw a dramatic shift in practice from implantation at >5 years of age at the start of the programme towards earlier implantation by the mid-1990s. Best language results were seen for implantation <5 years of age and duration of cochlear neuromodulation >4 years, hence implantation <1 year of age, indicating that severely deaf, pre-lingual children could benefit from cochlear neuromodulation if implanted early. Similar to initial CI use, the majority of children receiving DBS for dystonia in the first 9 years were 5–15 years of age, when the proportion of life lived with dystonia exceeds 90% thus limiting benefits. Conclusion: Early DBS neuromodulation for acquired motor disorders should be explored to maximise the benefits of dystonia reduction in a period of maximal developmental plasticity before the onset of disability. Learning from cochlear implantation, DBS can become an accepted management option in children under the age of 5 years who have a reduced proportion of life lived with dystonia, and not viewed as a last resort reserved for only the most severe cases where benefits may be at their most limited. Highlights: Cerebral palsies and childhood deafness have varied aetiology and similar incidence. Cochlear implantation is a highly successful neuromodulation in developing brains. Cochlear implantation in pre-lingual children results in best language development. Earlier DBS for dystonia could maximise motor development and reduce disability. Technological advances in DBS hardware could facilitate earlier implantation.